1999
DOI: 10.1590/s0100-736x1999000200004
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação experimental pelos frutos de Xanthium cavanillesii (Asteraceae) em ovinos

Abstract: Os frutos moídos de Xanthium cavanillesii foram administrados por via oral, em doses únicas ou fracionadas, a 15 ovinos adultos. Nove ovinos morreram. Doses a partir de 2 g/kg em uma única administração foram letais para os ovinos. Doses únicas de 1,25 g/kg e doses de 2,5 g/kg subdivididas em duas administrações diárias (1,25 g/kg em dois dias consecutivos) não causaram a intoxicação. Sinais clínicos foram observados apenas nos animais que morreram. Iniciavam entre 5 horas e 20 horas após o início da administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
14

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
(28 reference statements)
1
7
0
14
Order By: Relevance
“…Fibrin extravasation is an additional feature of tho se cavitary ϐluids because clots formed when the ϐluids were exposed to air. Similar ϐindings have been described in intoxications by Xanthium cavanillesii (Loretti et al 1999) and Microcystis aeruginosa (Jackson et al 1985).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Fibrin extravasation is an additional feature of tho se cavitary ϐluids because clots formed when the ϐluids were exposed to air. Similar ϐindings have been described in intoxications by Xanthium cavanillesii (Loretti et al 1999) and Microcystis aeruginosa (Jackson et al 1985).…”
Section: Discussionsupporting
confidence: 73%
“…Sinusoidal dilatation has been observed in Xanthium cavanillesii (Loretti et al 1999) and Microcystis aeruginosa (Jackson et al 1985) poisonings and indicates vascular lesions. Proliferation of the smooth endoplasmic reticulum has been associated with an increased production of detoxifying enzymes (Cheville 1994) and could explain an increased ability to metabolize toxins, consequently leading to the development of apparent tolerance observed here.…”
Section: Discussionmentioning
confidence: 99%
“…The whole plant has been used to treat bacterial infections, diabetes, skin pruritus, inflammatory diseases like rhinitis and rheumatoid arthritis, and cytotoxicity and antitumor activity (Kamboj & Saluja, 2010;Kumar & Rajkapoor, 2010;Patil et al, 2012;Aranjani et al, 2013). Despite the medicinal use, some investigations have reported that Xanthium strumarium induced intoxication and could be lethal to cattle (Colodel et al, 2000), sheep (Loretti et al, 1999), pigs (Stuart et al, 1981;Masvingwe & Mavenyengwa, 1998), and humans (Turgut et al, 2005). The results showed that the consumption of the fruits (burrs) induced hepatic necrosis, as well as myocardial injury in humans.…”
Section: Introductionmentioning
confidence: 99%
“…na fase com cotilédones (Witte et al 1990, Martin et al 1992, Méndez et al 1998. Há também semelhanças com a intoxicação pelos frutos de X. cavanillesii em ovinos (Loretti 1997) e X. strumarium em suí-nos (Stuart et al 1981).…”
Section: Discus Discus Discus Discus Discussão São São São Sãounclassified
“…Os sinais digestivos observados neste trabalho foram descritos em intoxicações naturais e experimentais com Xanthium spp. em bovinos (Martin et al 1986, Méndez et al 1998, ovinos (Loretti 1997, Méndez et al 1998) e suínos (Stuart et al 1981). Esses sinais clínicos ocorrem nas intoxicações de bovinos por outras plantas hepatotóxicas como Cestrum intermedium (Gava et al 1996), Cestrum corymbosum var.…”
Section: Discus Discus Discus Discus Discussão São São São Sãounclassified